Design and characterization of an radio frequency reused energy system for nano-devices - Haider Al-Mumen; Ahmed Abdulkadhim Hamad (Institute of Advanced Engineering and Science, 2022)
In this work a simple, high conversion efficiency, and high output voltage energy harvesting device was designed and simulated. The harvesting device consists of microstrip antennas, matching and rectifier circuits. Both mono patch and array antennas are designed to be operated at 5.8 GHz. The simulation work was implemented using central standard time (CST) studio. Results showed an accepted return loss and high gain. To more elevate the device gain and then to obtain greater output energy, an array of microstrip antennas was designed. To convert the radio frequency (RF) energy to dc output voltage, a rectifier, which consists of a voltage doubter and schottky diodes was designed using advanced design system (ADS) simulator. Furthermore, to achieve 50 Ω impedance, a matching circuit was designed by adjusting the microstrip line patterns. The output voltage of the device was 6.2 V at input power 20 dBm and 560 Ω load resistance.